(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
Newspapers in the princely state of Mysore played a pivotal role in shaping political consciousness and fostering nationalist sentiment between 1800 and 1947. Operating within a semi-autonomous governance structure, where formal political participation was limited, the press emerged as a vital medium for public discourse, civic engagement, and social advocacy. This study investigates the contributions of both English and Kannada newspapers in mobilizing public opinion, promoting socio-political reforms, and linking local populations to the broader Indian nationalist movement. Through the use of archival research, qualitative content analysis of editorials, opinion pieces, and letters to the editor, along with historical documentation, the study highlights the press’s multifaceted role as a catalyst for political awareness, social reform, and cultural nationalism. Findings reveal that newspapers did more than inform—they educated citizens on governance, civil rights, and social responsibilities, while simultaneously inspiring active participation in local and national campaigns for independence. English-language newspapers primarily influenced urban elites, fostering informed debate among professionals and decision-makers, whereas Kannada newspapers reached semi-urban and rural communities, promoting literacy, civic engagement, and grassroots mobilization. Editors frequently functioned as both chroniclers and activists, strategically bridging local concerns with national movements. Overall, the study underscores the enduring significance of print media in nation-building, demonstrating that even within the constraints of princely governance, newspapers were instrumental in cultivating political consciousness, social awareness, and a shared sense of national identity.